To Develop Simulations of Steel Roof Truss and Analysis of Impact of Different Input Parameters in Ansys (International Journal of Innovative Research in Engineering & Management, 2022)
A truss is an unchangeable shape made up  of many members linked at their ends in metallic structures.  Roof trusses are a common component of commercial  structures such as auditoriums, workplaces, garages, and  warehousing. Roof trusses are used to support roof inanimate  masses, living masses, and bending stress caused by wind  and disaster. In this study, Howe and Pratt's truss are used to  achieve extraordinary spans and eave heights. Four specific  spans of 5m, 10m, 15m, and 20m have been included, with  eave heights of 5m, 10m, 15m, and 20m, respectively. The  use of the STAAD pro software program and layout for  various structural variables such as Purlins has been  completed.
Keywords: Steel Trusses; Steel Structure; Optimisation; Architectural Effectiveness; Purlins